Species description and distribution of Strombus (Mollusca, Strombidae) in Johor Straits and its surrounding areas - Che Cob, Zaidi; Arshad, Aziz; Bujang, Japar Sidik; Abd. Ghaffar, Mazlan (Penerbit Universiti Kebangsaan Malaysia, 2009)
A total of 230 individuals of Strombus were sampled at various locations along the Johor Straits, Malaysia. There were four species of Strombus present in the study areas i.e. Strombus canarium Linnaeus, 1758; Strombus urceus Linnaeus, 1758; Strombus marginatus subspecies succinctus Linnaeus, 1767; Strombus marginatus subspecies robustus Sowerby, 1874; and Strombus vittatus subspecies vittatus Linnaeus, 1758. Strombus canarium was the most common, widely distributed and most abundant, followed by S. urceus, while the others were only rarely found. Among the species Strombus marginatus and Strombus vittatus were two new distribution records for the Johor Straits. Since all Strombus were traditionally harvested and consumed by the locals since long ago, further studies are needed particularly regarding the population dynamics and fishery of the harvested species.